PROSES PENGEMBALIAN KENDARAAN BERMOTOR YANG DIJADIKAN BARANG BUKTI DALAM PROSES PERADILAN DI KEJAKSAAN NEGERI KOTA PEKANBARU - Hb, Margerytha Wulandara; Effendi, Erdianto; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
In fact, there are many people / citizens were negligent in carrying out obligations so that has a violation of law. A person will be unlawful by the court and the judge can convict it if receiving at least two valid evidence in the court. Against each item of evidence which has been ready for use in the trial, or no needed or set aside for the public interest or not enough evidence, the evidence may be returned as set out in Article 46 paragraph (1) and (2) Criminal Procedure Code. Evidences include motor vehicles, knives, weapons, clothes, laptops, mobile phones and other objects related to use when committing a crime. In this case, the public prosecutor is given the authority by law to prosecute and execute the determination of the judge in the process of returning the evidence. However, in the process of return of evidences, especially motor vehicles, the prosecutor having problems and not just the prosecutor, the community also experienced problems to take their motor vehicles. Based on the above, the authors are interested doing research with the title of the return process in motor vehicles used as evidence in judicial proceess in the district attorney Pekanbaru. This essay aims to determine the return of motor vehicles used as evidence in judicial proceedings in the district attorney Pekanbaru City and also to understand the constraints faced by the prosecutor in the proceess of return the motor vehicles which used as evidence in judicial proceedings in the district attorney Pekanbaru City and to know what is done in an effort to overcome the obstacles in the return of motor vehicles used as evidence in judicial proceedings in the district attorney Pekanbaru. Based on the results the process of return the vehicle shall be furnished administrative requirements, the barriers faced by the prosecutor is an incompleteness of the requirements by the public administration, the court decisions returns the evidence to the defendant, the lack of facilities and infrastructures. While from the constraints of society is their must pay the fee for taking their motor vehicle. In an effort to overcome these obstacles, the prosecutor asked public to complete the administrative requirements, asked the defendants to contact their family to take the motor vehicle, make a report to the addition of facilities and infrastructures and add members of the personnel section of the exhibits. The conclution are the process of return motor vehicles are not in accordance with Article 46 of the Criminal Procedure Code and Case Management SOP General Crime, still not complete the administrative requirements of the public, the defendant did not contact the family, lack of facilities and infrastructures and members of the personnel section of the exhibits. The authors suggestion are motor vehicles should be returned quickly and easy so that people can conduct their activities.Keywords: Returns-Vehicle-Evidence-In Judicial Process